Effect of Reduced-Step Polishing Systems on Color Stability of Nanocomposites Submitted to Thermocycling Staining with Common Beverages - An In Vitro Study - Weam D. Naji; Manal H. Abd-Alla (Wolters Kluwer Medknow Publications, 2024)
Context Long-term color stability of composite resins is one of the most important factors influencing the clinical longevity of aesthetic restorations. Aims This study evaluated the effect of novel reduced steps and gold standard multiple steps polishing systems of two composite resins; a nano-filled (Filtek Z350XT) versus a supra-nanofill (Palfique LX5) on their color stability after submitting to thermocycling with common beverages. Materials and Methods Sixty disc-shaped specimens were fabricated from both composite resins (n = 30). From each material, ten specimens acted as the control group (Mylar strip), ten specimens were polished with Sof-Lex Diamond spirals, and ten were polished with Super-Snap X-Treme discs. All the specimens were thermocycled with staining solutions. Color was measured by a spectrophotometer before and after thermocycling and color difference (ΔE*) was calculated. Statistical Analysis Used One-way analysis of variance followed by Tukey's post-hoc test and independent t-test (α = 0.05) were used. Results A significantly highest color change was recorded for both control subgroups (P < 0.05), and the Sof-Lex Diamond spiral showed significantly the lowest color change (P < 0.05). Both the control and Sof-Lex Diamond spiral subgroups of Palfique LX5 produced significantly lower color change compared with subgroups of Filtek Z350 (P < 0.05). Conclusions Sof-Lex Diamond spiral polishing system provided the least color difference for both composites, while there was no significant difference between the materials when the Super-Snap X-Treme polishing system was used.